Transcutaneous auricular vagal nerve stimulation modulates blood glucose in ZDF rats via intestinal melatonin receptors and melatonin secretion - Zhang, Yuzhengheng; Zou, Ningyi; Xin, Chen; Wang, Yifei; Zhang, Zixuan; Rong, Peijing; Li, Shaoyuan (Frontiers in Neuroscience, 2024)
BackgroundMelatonin (MLT) and its receptor deficiency have been shown to be associated with type 2 diabetes mellitus (T2DM). Transcutaneous auricular vagus nerve stimulation (taVNS) is a non-invasive alternative intervention for patients suffering from hyperglycemia. Here, we aimed to investigate the role of taVNS on blood glucose modulation via intestinal melatonin receptors (MRs) and MLT secretion in hyperglycemia.MethodsAdult male Zucker diabetes fatty (ZDF) rats and Zucker lean (ZL) littermates were used. Forty ZDF rats were randomized into ZDF, taVNS, Px + taVNS and Lu + Px + taVNS groups (Px: pinealectomy, Lu: Luzindole). ZL rats served as a control group for comparison with ZDF rats without involvement in the taVNS intervention. Thirty min-taVNS interventions (2/15 Hz, 2 mA, 30 min/days) were administered once daily under anesthesia for 3 consecutive weeks in taVNS, Px + taVNS and Lu + Px + taVNS groups. Body weight and fasting blood glucose (FBG) were measured weekly in all rats, and real-time blood glucose was tested in the ZL and ZDF groups before, during and after the taVNS intervention. Plasma MLT concentration and the expression of MRs in the duodenum, jejunum and ileum were measured by the end of experiments.ResultsCompared with the ZL group, the level of FBG and body weight increased (all p < 0.01), plasma MLT secretion and the expression of MRs in duodenum, jejunum and ileum of ZDF rats decreased obviously (all p < 0.05), respectively. TaVNS can significantly reverse the hyperglycemia by regulating the non-pineal-derived MLT and MRs system in Px + taVNS group. Compared with the ZDF group, the expression of different intestinal MRs in the taVNS group was increased and more compactly arranged (both p < 0.05), the level of plasma MLT secretion was up-regulated (p < 0.01), and FBG and body weight were decreased (both p < 0.01). Meanwhile, after taVNS intervention in rats in the Px + taVNS group, we observed an increase in MLT secretion and the number of intestinal MRs compared with the taVNS group (all p > 0.05). In contrast, ZDF rats in which the pineal gland was excised by taVNS intervention and injected with the MRs antagonist Luzindole did not show these changes.ConclusionThe glucose reduction effect of taVNS may be related to regulating MLT levels and expressing intestinal MRs.